Pengaruh Fasilitas Kerja, Etika Kerja Dan Komunikasi Terhadap Kepuasan Kerja Pada Pegawai PT. Samudera Lautan Luas Medan - Maulana, Rizky; Tahura, T. Lyza; Fahlevi, Alvin (Jurnal EMT KITA, 2023)
This study aims to analyze the influence of work facilities, work ethics and communication on employee job satisfaction. The total population in this study was 110 people, and by using the saturated sampling technique, a sample of 110 people was obtained. The analysis technique used is multiple linear regression. The results showed that work facilities had a significant effect on employee job satisfaction at PT Samudera Lautan Luas Medan, work ethics had a significant effect on employee job satisfaction at PT Samudera Lautan Luas Medan, communication had no effect on employee job satisfaction at PT Samudera Lautan Luas Medan. Simultaneously it shows that work facilities, work ethics and communication have a significant effect on employee job satisfaction at PT Samudera Lautan Luas Medan.